2004
DOI: 10.1007/s00203-004-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric conjugal transfer of plasmid DNA from Escherichia coli to Kitasatospora setae , a bafilomycin B 1 producer

Abstract: An effective transformation procedure for Kitasatospora setae was established based on transconjugation from Escherichia coli ET12567 (pUZ8002) using a phi C31-derived integration vector, pSET152, containing oriT and attP fragments. While no transconjugation was observed under the standard transconjugation conditions for Streptomyces species, sufficient transconjugation (>1 x 10(-6)) was achieved on ISP4 medium containing 30 mM MgCl(2) using a 25- to 125-fold excess of E. coli donor cells. In addition, the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 22 publications
6
50
1
Order By: Relevance
“…The recombinant DNA may be introduced into K. setae by an E. coli/ Streptomyces conjugation using an IncP-plasmid (RK2) origin transfer. 34,35 However, we found that the transformation of K. setae KM-6054 was improved by electroporation (approximately 10-to 100-fold higher than the conjugation with E. coli and IncP-plasmid). K. setae generated submerged spores in the liquid culture and DNA was introduced into the submerged spores by electroporation.…”
Section: Characterization Of Bafilomycin Biosynthesismentioning
confidence: 83%
“…The recombinant DNA may be introduced into K. setae by an E. coli/ Streptomyces conjugation using an IncP-plasmid (RK2) origin transfer. 34,35 However, we found that the transformation of K. setae KM-6054 was improved by electroporation (approximately 10-to 100-fold higher than the conjugation with E. coli and IncP-plasmid). K. setae generated submerged spores in the liquid culture and DNA was introduced into the submerged spores by electroporation.…”
Section: Characterization Of Bafilomycin Biosynthesismentioning
confidence: 83%
“…In the case of Kitasatospora setae conjugation, the use of 2.5 × 10 7 E. coli as donor yielded no exconjugants, but a further increase in the number of E. coli facilitated the conjugal transfer of K. setae (Choi et al 2004). As shown in Table 2, when 1 × 10 4 spores were used as the recipient for conjugation, the transconjugation frequency was proportionately improved with increasing numbers of E. coli donor.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters affecting transconjugation efficiency To select an optimal medium for the conjugal transfer of S. cinnamoneus, four media (AS-1, ISP2, ISP4, and MS) were tested because the effect of medium for the successful conjugal transfer of actinomycetes is absolute (Bierman et al 1992;Flett et al 1997;Choi et al 2004). AS-1, ISP4, and MS are representative media for the conjugal transfer of actinomycetes and ISP2 is an optimal medium for growth and spore formation of S. cinnamoneus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations